PENGARUH KEPEMIMPINAN PRIMAL DAN PROFESIONALISME TERHADAP KINERJA MELALUI KEPUASAN KERJA (Studi Kasus pada Perwira Pertama dan Perwira Menengah di Lingkungan Mabes Polri) - Baenur Fitry, Siti; Wirawan; Supriyadi, Edy (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2017)
This research aims to know the influence of Primal Leadership and Professionalism on Performance through Job Satisfaction of Polri Members. This type of research is an explanatory research with quantitative approach. To test the hypothesis and to produce a fit model, this research uses Structural Equation Modeling (SEM) with a variance based or component-based approach with Partial Least Square (PLS). With the number of samples as many as 198 members of the Police in the Police Headquarters neighborhood. The data source was obtained from the primary data by spreading the questionnaire and secondary data. This study uses Path Analysis (Path Analysis) with the help of SPSS 22.0 software. The results of this research showed that the primal leadership had a significant effect on job satisfaction, Professionalism had a significant effect on Job Satisfaction, Primal Leadership had a significant effect on Performance, Professionalism had significant influence to Performance and Job Satisfaction had significant influence to Performance.